New students – old sins: elephant in the (lab)room - Gotfryd, Kamil (Improving University Science Teaching and Learning, 2023)
Laboratory exercises are important in science education as they contribute to general understanding of the topics presented in lectures and enable students to acquire hands-on experience of the scientific research. However, conscious participation in the practical courses allowing for complete achievement of their learning outcomes depends on the proper prelaboratory preparation. Unfortunately, it is a common problem that students show up under-prepared to participate in the laboratory sessions. This study focuses on medical students, and analyses the level of their pre-laboratory preparation, used techniques, resources and motivational force of the activities. The results show that students do not spend enough time for the preparation and do not use online-based materials. The main reason for under-preparation turns out to be the lack of time. This project discusses also implementation of the possible motivational activities that could enhance the student preparedness and overall performance in the laboratory.